(untitled) ("Journal "U". Economy. Management. Finance.", 2025)
The paper examines theoretical and applied aspects of increasing the effectiveness of advertising campaigns through the use of digital communications. The study analyzed key online advertising formats, including banner, search, social, mobile advertising and email marketing, and highlighted their features and advantages in terms of personalization, targeting and interactivity. The use of statistical data on user digital behavior made it possible to justify the choice of the most promising communication channels. Particular attention is paid to analytical tools for assessing the effectiveness of advertising activities, including ROI, CPA and CTR. A conclusion is made about the need for an integrated approach to developing a digital strategy, including channel selection, content adaptation and ongoing monitoring of results.